Is the Future of Energy Rotten? Novel Perspective on Tri-Phase Fermentation and the Food Waste Paradox - Paul Latiza, Rich Jhon; Rubi, Rugi Vicente; Olay, Jerry; Soriano, Allan (Applied Science and Engineering Progress, 2025)
Annually, a staggering 1.3 billion tons of edible food are wasted globally, representing not only a substantial economic loss but also a squandered opportunity for sustainable energy production. While anaerobic digestion offers a potential pathway for valorizing this waste, its limitations in feedstock conversion efficiency and substrate versatility necessitate the exploration of innovative alternatives. This comprehensive perspective review elucidates the transformative potential of tri-phase fermentation (TPF), a groundbreaking approach that represents a paradigm shift in waste valorization by synergistically integrating solid-state fermentation (SSF), submerged fermentation (LF), and gas fermentation (GF) to derive bioethanol from food waste. This study highlights the successful integration of these three phases within the TPF framework, demonstrating effective carbohydrate breakdown in SSF, significant ethanol production in LF, and valuable product generation from syngas in GF. By harnessing the metabolic capabilities of diverse microorganisms and leveraging emerging technologies, TPF offers a holistic solution, effectively converting both the primary food waste and its residual byproducts into valuable bioethanol. This review critically examines the fundamental principles, comparative advantages, and inherent challenges associated with each fermentation phase, while also elucidating their potential for synergistic integration within the TPF framework. Furthermore, the technological and economic hurdles inherent to TPF are addressed, emphasizing the need for further research in strain engineering, process optimization, and downstream processing to enhance its commercial viability. This review accentuates and provides a comprehensive perspective on the urgent need for further research and development to fully unlock the transformative potential of TPF and promote a circular bioeconomy by converting food waste into valuable bioethanol, addressing both waste and energy challenges.